2021
DOI: 10.3389/fbioe.2021.653033
|View full text |Cite
|
Sign up to set email alerts
|

Bombyx mori Silk Fibroin Regeneration in Solution of Lanthanide Ions: A Systematic Investigation

Abstract: Silk Fibroin (SF) obtained from Bombyx mori is a very attractive biopolymer that can be useful for many technological applications, from optoelectronics and photonics to biomedicine. It can be processed from aqueous solutions to obtain many scaffolds. SF dissolution is possible only with the mediation of chaotropic salts that disrupt the secondary structure of the protein. As a consequence, recovered materials have disordered structures. In a previous paper, it was shown that, by modifying the standard Ajisawa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
(63 reference statements)
0
16
0
Order By: Relevance
“…Our previous investigations led to the discovery of a new dissolution and fiber regeneration procedure involving CeCl 3 ·7H 2 O . Starting from this evidence, a systematic investigation of all of the lanthanide ions as chaotropic agents was performed . The results of this study showed the unique ability of each lanthanide ion to dissolve SF and to regenerate it with different degrees of crystallinity depending on the metal used. However, the fine molecular architecture of the Ln–SF fibers, in terms of the exact amount of the secondary structure and of crystalline content for each sample, remained not fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous investigations led to the discovery of a new dissolution and fiber regeneration procedure involving CeCl 3 ·7H 2 O . Starting from this evidence, a systematic investigation of all of the lanthanide ions as chaotropic agents was performed . The results of this study showed the unique ability of each lanthanide ion to dissolve SF and to regenerate it with different degrees of crystallinity depending on the metal used. However, the fine molecular architecture of the Ln–SF fibers, in terms of the exact amount of the secondary structure and of crystalline content for each sample, remained not fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Biomaterials derived from natural sources, including proteins and peptides, provide a unique opportunity to create biocompatible structures for biomedical applications. , The self-assembly of these protein molecules can lead to functional complexes that have tunable three-dimensional structures, ranging in size from nanometers to centimeters. Furthermore, these structures offer promising routes for loading, carrying, and releasing cargo molecules to selected targets. More importantly, protein-based structures are nontoxic, nonimmunogenic, biodegradable, and biocompatible, making them ideal candidates for drug/gene delivery applications. A group of materials that distinctly match these applications due to their biobased components are silk-derived proteins. ,, In its natural role, native silk fibroin (NSF) is spun into long fibers by the Bombyx mori silkworm, resulting in strong hydrogen bonding within β-sheet nanocrystallites that have both highly ordered and amorphous regions, giving the silk threads their durable mechanical properties. , NSF can be dissolved to form regenerated silk fibroin (RSF), , resulting in a new material that is a natural block copolymer, which can be readily reassembled into bespoke structures that retain many of the attractive chemical and physical properties that native silk possesses, including durability, biocompatibility, and tunability . These qualities make it an excellent resource in medical materials, tissue engineering, and in the delivery of therapeutics, with the advantage that RSF can be handled with greater ease than its native counterpart .…”
Section: Introductionmentioning
confidence: 99%
“…To circumvent this, we dissolved silk fibers with non-toxic and biocompatible calcium nitrate tetrahydrate. The regenerated silk fibroin (RSF) was biophysically characterized to confirm its natural characteristics [8].…”
Section: Introductionmentioning
confidence: 99%